Developing a competency scale for sport coaches - De Klerk, N.; Surujlal, J. (African Journal for Physical, Health Education, Recreation and Dance, 2014)
The importance of operational competencies of sport coaches is widely acknowledged in the literature, yet there appears to be a lack of research in this field. The purpose of this research study was to develop a competency scale for sport coaches. Based on literature regarding operational competencies of sport coaches, an empirical study was conducted to identify the most important competencies, using multiple-item indicators from previous studies. A quantitative research approach was employed, whereby a questionnaire survey was conducted in order to develop a competency scale for sport coaches. The findings of the study provide important insights into the operational competencies required by sport coaches based on an empirical investigation of the perceptions of sport coaches. The findings of this study can be implemented to develop training programmes for sport coaches; develop performance appraisal tools and assist coaches in addressing areas of deficiency regarding their ability to coach.